Creation of dialysis vascular access with normal flow increases brain natriuretic peptide levels - Malík, Jan; Tuka, Vladimir; Krupickova, Zdislava; Chytilova, Eva; Holaj, Robert; Slavikova, Marcela (International urology and nephrology, 2009)
BACKGROUND: Chronic heart failure is very common in hemodialyzed patients due to several factors such as intermittent volume overload, anemia, and hypertension. Dialysis access flow is usually considered to have a minor effect. We hypothesized that creation of dialysis access with "normal" flow would lead to elevation of B-type natriuretic peptide (BNP), which is a sensitive marker of heart failure. METHODS: We included subjects with a newly created, well-functioning vascular access and normal left ventricular ejection fraction. They were examined before access creation (baseline), then again 6 weeks and 6 months after the surgery. Only subjects with access flow (Qa) < 1500 ml/min were included. Changes of BNP levels and their relation to access flow were studied. RESULTS: We examined 35 subjects aged 60.6 +/- 13.5 years. Qa was 789 +/- 361 and 823 +/- 313 ml/min at 6 weeks and 6 months after the surgery, respectively. Within 6 weeks after access creation, BNP rose from 217 (294) to 267 (550) ng/l (median (quartile range)) with P = 0.003. Qa was significantly related to BNP levels 6 weeks after access creation (r = 0.37, P = 0.036). Six months after access creation, there was only a trend of BNP decrease (235 (308) ng/l, P = 0.44). Creatinine, blood urea nitrogen and hemoglobin levels as well as patients' weight did not change significantly. CONCLUSIONS: Creation of dialysis access with "normal" flow volume leads to significant increase of BNP, which is related to the value of access flow. The increase of BNP probably mirrors worsening of clinically silent heart failure.
Keywords: Kidney Failure, Chronic; Sensitivity and Specificity; senzitivita a specificita; Humans; Renal Circulation; Heart Failure; srdeční selhání; lidé středního věku; Disease Progression; Arteriovenous Shunt, Surgical; kohortové studie; Renal Dialysis; natriuretický peptid typu B; Female; Aged; analýza rozptylu; Analysis of Variance; dialýza ledvin; senioři; lidé; Biomarkers; Normal Distribution; renální oběh; Regression Analysis; normální rozdělení; časové faktory; Cohort Studies; Follow-Up Studies; biologické markery; ženské pohlaví; chronické selhání ledvin; Male; Middle Aged; arteriovenózní zkrat; dysfunkce levé srdeční komory; Ventricular Dysfunction, Left; progrese nemoci; Natriuretic Peptide, Brain; Risk Assessment; mužské pohlaví; Time Factors; hodnocení rizik; regresní analýza; následné studie